Immunomodulatory Potential of Fungal Extracellular Vesicles: Insights for Therapeutic Applications - Nenciarini, Stefano; Cavalieri, Duccio (Biomolecules (Basel, Switzerland), 2023)
Extracellular vesicles (EVs) are membranous vesicular organelles that perform a variety of biological functions including cell communication across different biological kingdoms. EVs of mammals and, to a lesser extent, bacteria have been deeply studied over the years, whereas investigations of fungal EVs are still in their infancy. Fungi, encompassing both yeast and filamentous forms, are increasingly recognized for their production of extracellular vesicles (EVs) containing a wealth of proteins, lipids, and nucleic acids. These EVs play pivotal roles in orchestrating fungal communities, bolstering pathogenicity, and mediating interactions with the environment. Fungal EVs have emerged as promising candidates for innovative applications, not only in the management of mycoses but also as carriers for therapeutic molecules. Yet, numerous questions persist regarding fungal EVs, including their mechanisms of generation, release, cargo regulation, and discharge. This comprehensive review delves into the present state of knowledge regarding fungal EVs and provides fresh insights into the most recent hypotheses on the mechanisms driving their immunomodulatory properties. Furthermore, we explore the considerable potential of fungal EVs in the realms of medicine and biotechnology. In the foreseeable future, engineered fungal cells may serve as vehicles for tailoring cargo- and antigen-specific EVs, positioning them as invaluable biotechnological tools for diverse medical applications, such as vaccines and drug delivery.